Value of clinical tests in diagnosing anterior cruciate ligament injuries: A systematic review and meta-analysis. Issue 31 (5th August 2022) - Huang, Zhihao; Liu, Zhihao; Fan, Changfeng; Zou, Miao; Chen, Jiyan
Abstract : Objectives: This study compared 4 clinical tests with reference to magnetic resonance imaging and arthroscopic visualization to comprehensively evaluate their diagnostic value for anterior cruciate ligament injuries. Methods: We systematically searched 10 electronic databases from January 1, 2010, to May 1, 2021. Two reviewers collected data in accordance with the Preferred Reporting Item for Systematic Reviews and Meta-Analyses 2020 guidelines. The quality of each study was assessed using the Quality Assessment of Diagnostic Accuracy Studies 2 tool. A meta-analysis was performed using Meta-Disc version 1.4 and Stata SE version 15.0. Results: Eighteen articles involving 2031 participants were included. The results of the meta-analysis showed that for the Lachman test, the pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnosis odds ratio, area under the curve (AUC) of summary receiver operating characteristic (SROC), and Q* were 0.76 (95% CI, 0.73–0.78), 0.89 (95% CI, 0.87–0.91), 5.65 (95% CI, 4.05–7.86), 0.28 (95% CI, 0.23–0.36), 22.95 (95% CI, 14.34–36.72), 0.88, and 0.81, respectively. For the anterior drawer test, the pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnosis odds ratio, AUC of SROC, and Q* were 0.64 (95% CI, 0.61–0.68), 0.87 (95% CI, 0.84–0.90), 3.57 (95% CI, 2.13–5.96), 0.44 (95% CI, 0.32–0.59), 8.77 (95% CI, 4.11–18.74), 0.85, and 0.78, respectively. For the pivot shift test, the pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnosis odds ratio, AUC of SROC, and Q* were 0.59 (95% CI, 0.56–0.62), 0.97 (95% CI, 0.95–0.98), 13.99 (95% CI, 9.96–19.64), 0.44 (95% CI, 0.35–0.55), 29.46 (95% CI, 15.60–55.67), 0.98, and 0.94, respectively. For the lever sign test, the pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnosis odds ratio, AUC of SROC, and Q* were 0.79 (95% CI, 0.75–0.83), 0.92 (95% CI, 0.87–0.95), 9.56 (95% CI, 2.76–33.17), 0.23 (95% CI, 0.12–0.46), 47.38 (95% CI, 8.68–258.70), 0.94, and 0.87, respectively. Conclusions: Existing evidence shows that these clinical tests have high diagnostic efficacy for anterior cruciate ligament injuries, and that every test has its own advantages and disadvantages. However, the above results should be validated through additional studies, considering the limited quality and quantity of our sample.